Central America - Amador Astúa, Jorge Alberto (2017)
Central America experienced anomalies in temperature and precipitation in 2016. Mean temperatures were higher than average, particularly in Puerto Barrios, Choluteca, and San José. The increase in mean temperatures was due to more frequent warm days. In terms of precipitation, David, San José, Puerto Barrios, and Puerto Lempira had above-average accumulations, with Puerto Lempira experiencing extremely high accumulations at the end of the year. Conversely, Tocumen, Liberia, Choluteca, Belize, and Limón had below-average precipitation. Drought conditions persisted in Liberia for the fourth consecutive year. Additionally, three tropical cyclones, namely Hurricane Earl, Hurricane Matthew, and Hurricane Otto, impacted Central America in 2016, causing heavy rain, floods, and significant damage in Belize, Guatemala, Costa Rica, Nicaragua, and Panama. Hurricane Otto was particularly noteworthy as it broke several historical records and produced intense lightning activity and precipitation in Nicaragua and Costa Rica. In summary, Central America experienced higher mean temperatures, varied precipitation patterns, and the impacts of three tropical cyclones in 2016. The region observed anomalies in temperature, with warmer temperatures than the climatology. Precipitation patterns were diverse, with some areas experiencing above-average accumulations while others faced below-average precipitation and prolonged drought conditions. The tropical cyclones, especially Hurricane Otto, brought significant rainfall, flooding, and damage to several countries. These events highlight the importance of monitoring and understanding climate patterns and their impacts on the region's ecosystems and communities.